COGNITIVE RESEARCH IN EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The given article reviews the role of cognitive theory in education. At a time when knowledge has become the main source for modern innovative education and economics, in order to develop scientific and creative knowledge, cognitive research plays the main role in education. Jean Piaget could prove it in his theory. Cognitive education is education that seeks to improve the cognitive (mental) skills of the student in order that the students can lead constructive and satisfying lives.